An Integrative Pharmacology Model for Decoding the Underlying Therapeutic Mechanisms of Ermiao Powder for Rheumatoid Arthritis - Wu, Jie; Wang, Kexin; Liu, Qinwen; Li, Yi; Huang, Yingying; Liu, Yujie; Cai, Jieqi; Yin, Chuanhui; Li, Xiaowei; Yu, Hailang; Meng, Wei; Wang, Handuo; et al. (Frontiers in Pharmacology, 2022)
As a systemic inflammatory arthritis disease, Rheumatoid arthritis (RA) is complex and hereditary. Traditional Chinese medicine (TCM) has evident advantages in treating complex diseases, and a variety of TCM formulas have been reported that have effective treatment on RA. Clinical and pharmacological studies showed that Ermiao Powder (EMP) which consists of Phellodendron amurense Rupr (PAR) and Atractylodes lancea (Thunb.) DC. (ALD) can be used in the treatment of RA. Currently, most researches focused on the anti-inflammatory mechanism of PAR and ALD respectively and less focused on the co-ordinated molecular mechanism of them. In this research, we established an integrative pharmacological strategy to explore the co-ordinated molecular mechanism of the 2 herbs of EMP in treating RA. To explore the potential co-ordinated mechanism of PAR and ALD, we firstly developed a novel mathematical model to calculate the contribution score of 126 active components, and 85 active components which contributed 90% of the total contribution score were retained to construct the co-ordinated functional space. Then, the knapsack algorithm was applied to identify the core co-ordinated functional components from the 85 active components. Finally, we obtained the potential co-ordinated functional components group (CFCG) with 37 components. And functional enrichment analysis was performed on the targets of CFCG to explore the potential co-ordinated molecular mechanisms of PAR and ALD. The results indicated that the CFCG can treat RA by co-ordinated targeting to the genes involved in immunity and inflammation-related signal pathways, such as PI3K-Akt signaling pathway, MAPK signaling pathway, TNF signaling pathway, and NF-kappa B signaling pathway. The docking and vitro experiments were used to predict the affinity and validate the effect of CFCG, and further confirm the reliability of our method. Our integrative pharmacological strategy including CFCG identification and verification can provide the methodological references for exploring the co-ordinated mechanism of TCM in treating complex diseases, and contribute to improving our understanding of the co-ordinated mechanism.